An Alternative σ Factor, σ8, Controls Avermectin Production and Multiple Stress Responses in Streptomyces avermitilis - Sun, Di; Wang, Qian; Chen, Zhi; Li, Jilun; Wen, Ying (Frontiers in Microbiology, 2017)
Alternative σ factors in bacteria redirect RNA polymerase to recognize alternative promoters, thereby facilitating coordinated gene expression necessary for adaptive responses. The gene sig8 (sav_741) in Streptomyces avermitilis encodes an alternative σ factor, σ8, highly homologous to σB in Streptomyces coelicolor. Studies reported here demonstrate that σ8 is an important regulator of both avermectin production and stress responses in S. avermitilis. σ8 inhibited avermectin production by indirectly repressing expression of cluster-situated activator gene aveR, and by directly initiating transcription of its downstream gene sav_742, which encodes a direct repressor of ave structural genes. σ8 had no effect on cell growth or morphological differentiation under normal growth conditions. Growth of a sig8-deletion mutant was less than that of wild-type strain on YMS plates following treatment with heat, H2O2, diamide, NaCl or KCl. sig8 transcription was strongly induced by these environmental stresses, indicating response by σ8 itself. A series of σ8-dependent genes responsive to heat, oxidative and osmotic stress were identified by EMSAs, qRT-PCR and in vitro transcription experiments. These findings indicate that σ8 plays an important role in mediating protective responses to various stress conditions by activating transcription of its target genes. Six σ8-binding promoter sequences were determined and consensus binding sequence BGVNVH-N15-GSNNHH (B: C, T or G, V: A, C or G, S: C or G, H: A, C or T, N: any nucleotide) was identified, leading to prediction of the σ8 regulon. The list consists of 940 putative σ8 target genes, assignable to 17 functional groups, suggesting the wide range of cellular functions controlled by σ8 in S. avermitilis.